PENGARUH METODE TALAQQI TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN SISWA MADRASAH ALIYAH AL-USMANIYAH DI BAGAN BATU KABUPATEN ROKAN HILIR - Riski Sefrianti; Risnawati; Nasir Za’ba (STAI Nurul Falah Airmolek, 2024)
Penelitian ini di latar belakangi oleh rendahnya kemampuan siswa dalam membaca Al-Qur’an. Jenis penelitian ini merupakan penelitian kuantitatif korelasi. Fokus masalah pada penelitian ini adalah apakah terdapat pengaruh Metode Talaqqi terhadap Kemampuan Membaca Al-Qur’an Siswa Madrasah Aliyah Al-Usmaniyah di Bagan Batu Kabupaten Rokan Hilir. Penelitian ini bertujuan untuk mengetahui Pengaruh Metode Talaqqi terhadap Kemampuan Memb This research was motivated by the low ability of students to read the Koran. This type of research is quantitative correlation research. The focus of the problem in this research is whether the influence of the Talaqqi Method on the Al-Qur'an Reading Ability of Al-Usmaniyah Madrasah Aliyah Students in Bagan Batu, Rokan Hilir Regency. This research aims to determine the effect of the Talaqqi method on the ability to read the Al-Qur'an of Madrasah Aliyah Al-Usmaniyah students in Bagan Batu, Rokan Hilir Regency. The subjects used in this research were all class XII students of Madrasah Aliyah Al-Usmaniyah in Bagan Batu. The population of this research was 55 students in class XII of Madrasah Aliyah Al-Usmaniyah, 29 students in science class and 26 students in social studies class. This research consists of two variables, namely the Talaqqi Method (variable X) and the Ability to Read the Al-Qur'an (variable Y). The results of this research show that there is an influence of the talaqqi method on the ability to read the Al-Qur'an. This can be seen from the results of data processing using IBM SPSS statistics 22 for windows, that a simple regression analysis obtained a significant value smaller than 0.05, namely 0.024 < 0.05, so the hypothesis of this research is that there is an influence of the Talaqqi Method on the ability to read Al-Qur'an. Qur'an for Class XII Students of Madrasah Aliyah Al-Usmaniyah in Bagan Batu, Rokan Hilir Regency. The level of influence between the Talaqqi Method (variable This means that the influence of using the Talaqqi Method on the Al-Qur'an Reading ability of Al-Usmaniyah Madrasah Aliyah Students in Bagan Batu, Rokan Hilir Regency is in the